Offline printed Sindhi optical text recognition: survey - Solangi, Yasir Ali; Solangi, Zulfiqar; Raza, Ali; Ahmed Shaikh, Noor; Mallah, Ghulam Ali; Shah, Asadullah (Institute of Electrical and Electronics Engineers Inc., 2019)
Optical Charter Recognition (OCR) applications are becoming more intensive than before and show great prospective for rapid data entry, but has limited success when applied to the Sindhi language. This paper summarize the general topic of optical character recognition and highlights the characteristics of Sindhi script. It also presents an historical review of the Sindhi text recognition systems. More this paper underlines the capabilities of different OCT=R systems, and then introduce a five stage model for off-line printed Sindhi text recognition system and classify research work according to this model